An assessment of hygienic practices of utensils used by selected food establishments in Intramuros, Manila - Junio, April Jane M. Mangaran, Joyce Anne J. Natividad, Stephanie Q. Ornales, Lorenz Terese P. Pacquiz, Jennica D. Tan, Darleen Anne O. 4 0 16; 5 (2015)
NO ABSTRACT.
Undergraduate Thesis: (B.S. in Hotel and Hospitality Management) - Pamantasan ng Lungsod ng Maynila 2015.
Keywords: 2 -- 0; 6; 20; 20; 2